Individualism or complementarity? The effect of digital personal networks on face-to-face personal networks. - Requena-Santos, Félix; Ayuso-Sánchez, Luis Manuel (Taylor & Francis, 2018)
Information and communication technologies (ICTs) are affecting ways of networking in advanced societies. This study analyzes the interaction of face-to-face social networks and digital social networks in Spain, a Mediterranean country characterized by significant sociability in every social sphere. Our aim is to contrast this with the hypothesis that new forms of networking can lead to isolation or individualization. This study uses two surveys carried out by the Centro de Investigaciones Sociológicas [Center for Sociological Research] in 2014 and 2016, involving 4922 people over 18 years of age who were asked about these two types of networks (face-to-face and digital) and other topics related to demographics, family, social position, and personality traits. The results indicate complementarity between networks: digital networks served to enrich face-to-face networks, especially when people described themselves as extraverted. However, nuances were observed in relation to rural or urban habitat and forms of coexistence among those interviewed.
Keywords: Redes sociales; Redes sociales en Internet; Sociedad de la información; Social support networks; Virtual social networks; Sociability; Information and communication technologies